Growth, carcase characteristics, meat quality, nutrient digestibility and immune function of broilers fed with enzymatically treated or raw dandelion (taraxacum mongolicum hand.-mazz.). Issue 1 (31st December 2022) - Du, Juan; Zhao, Yang; Wang, Yuan; Xie, Mingxin; Wang, Ruifang; Liu, Na; An, Xiaoping; Qi, Jingwei
Abstract: This study aims at evaluating the effects of enzymatically treated or raw dandelion ( Taraxacum mongolicum Hand.-Mazz.) on growth performance, carcase characteristics, meat quality, apparent nutrient digestibility, and immunity of Arbour Acres broilers for 42 d. One hundred and twenty 1-day-old birds were randomly distributed into three treatments: basal diet (CON), basal diet plus 1 g/kg of raw dandelion (RD) and enzyme-treated dandelion (ED). The results shown that ED significantly decreased feed conversion ratio during the starter period (1–21 d). ED significantly increased apparent nutrient digestibility of ether extract and organic matter (OM) (1–21 d) as well as crude protein (22–42 d). RD significantly increased the OM nutrient digestibility (1–21 d). ED groups had significantly higher breast muscle rate, lower drip loss and water-holding capacity (WHC) in breast muscle, and lower cooking loss in leg muscle. RD significantly decreased breast muscle WHC. The serum immunoglobulin (Ig) A and IgG (d 21 and 42) as well as IgM (d 21) levels were observed higher in response to ED supplementation. RD treatment showed significantly higher serum IgA level at d 21. Additionally, dietary ED supplementation resulted in higher serum interleukin 10 (d 21) and interferon-γ (d 42) contents. In conclusion, ED displayed superior effects on improving feed conversion ratio, carcase characteristics, meat quality, apparent nutrient digestibility, and immune function of broilers. Highlights: Enzymatically treated (ED) and raw dandelion (RD) were evaluated in broiler chicken. ED improved feed conversion ratio and breast muscle rate. ED and RD enhanced meat quality, nutrient digestibility and immune function. ED had more beneficial effects than RD.